Comparative evaluation of non-contrast MRI versus gadoxetic acid-enhanced abbreviated protocols in detecting colorectal liver metastases - Haoran Dai; Cheng Yan; Xi Jia; Yuyao Xiao; Xinyue Liang; Chun Yang; Kai Liu; Mengsu Zeng (Insights into Imaging)
Abstract Purpose This study compares the diagnostic efficacy of non-contrast abbreviated MRI protocols with Gadoxetic acid-enhanced abbreviated MRI for detecting colorectal liver metastasis (CRLM), focusing on lesion characterization and surveillance. Methods Ninety-four patients, including 55 with pathologically verified CRLM, were enrolled, totaling 422 lesions (287 metastatic, 135 benign). Two independent readers assessed three MRI protocols per patient: Protocol 1 included non-contrast sequences (T2-weighted turbo spin-echo, T1-weighted Dixon, diffusion-weighted imaging (DWI), and ADC mapping). Protocol 2 included gadoxetic acid enhancement with hepatobiliary phase imaging, T2 TSE, DWI, and ADC maps. Protocol 3 utilized the standard Gadoxetic Acid-enhanced MRI sequence, which included pre-contrast T1-weighted imaging, T1-weighted Dixon sequences, post-contrast T1-weighted imaging (including arterial, portal venous, transitional and hepatobiliary phases), and additional T2-weighted and DWI sequences. Diagnoses were scored on a 5-point scale (benign = 1; malignant = 5), with scores ≥ 3 indicating CRLM. ROC curves analyzed diagnostic accuracy, comparing area under the curve (AUC) values across protocols. Results No significant difference in AUCs was observed between Protocol 1 (0.899–0.909) and Protocol 2 (0.906–0.931) versus Protocol 3 (0.935–0.939) (p = 0.091–0.195). For lesions ≤ 10 mm, Protocol 1 was slightly inferior to Protocol 3 (p = 0.002–0.032), while Protocol 2 remained comparably effective (p = 0.096–0.179). These findings held when using a threshold of ≥ 4 to define CRLM. Conclusion The non-enhanced abbreviated MRI protocol is as effective as the gadoxetic acid-enhanced protocol in identifying CRLM. The proposed Ab-MRI approach may be a viable alternative for CRLM surveillance. Critical relevance statement The non-enhanced abbreviated MRI (Ab-MRI) protocol is as effective as the gadoxetic acid-enhanced protocol in identifying colorectal liver metastasis (CRLM). The proposed Ab-MRI approach may be a viable alternative for CRLM surveillance. Key Points Two abbreviated protocols are proposed for colorectal liver metastasis (CRLM) surveillance. The non-enhanced protocol showed equivalent efficacy and was more cost-effective. The non-enhanced protocol may be a viable alternative for CRLM surveillance. Graphical Abstract